The Influence of Corporate Governance and Company Characteristics on the Performance of Manufacturing Companies Listed on the Indonesian Stock Exchange - Hadyan, Kamal; Mahsa Hisanah Dalilah; Alif Satria Ichsan; Henny Setyo Lestari (Jurnal Manajemen (Edisi Elektronik), 2024)
This study aims to determine the effect of corporate governance and company characteristics towards manufacturing companies’ firm performance for the period of 2018-2022. The independent variables included in this study are board size and CEO age as the measurement of corporate governance. Moreover, firm size, firm leverage, and firm age are also used as the measurements of the company characteristics variables. Return on equity and return on assets are used in this study to measure the firm performance as the dependent variable. This study used a quantitative approach method, and the sample was taken by using purposive sampling method which then resulted in 40 food & beverage subsector manufacturing companies that met the sampling characteristics. The data processed using EViews 10 to analyze the multiple linear regression. The results indicate that firm leverage and firm age have a significant effect on firm performance. Meanwhile, the other variables, namely board size, CEO age, and firm size have no influence on firm performance. The results obtained from this study are expected to be useful for company management to analyze the corporate governance and company characteristics towards firm performance and put more attention to variables that have a major influence on firm performance so that the company's survival can be maintained in the future.